2000
DOI: 10.1007/s004120000090
|View full text |Cite
|
Sign up to set email alerts
|

An immunoelectron study of karyosphere and nuclear bodies in oocytes of mealworm beetle, Tenebrio molitor (Coleoptera: Polyphaga)

Abstract: The karyosphere and nuclear bodies (NBs) were studied in Tenebrio molitor oocytes using immunoelectron cytochemistry. During early diplotene (previtellogenic stage), oocyte chromosomes begin to unite in a small nuclear volume forming the karyosphere. In vitellogenic oocyte nuclei, the chromatin undergoes condensation, and the karyosphere acquires a ring-shaped structure. The karyosphere is the only structure containing DNA in the oocyte nucleus. Pre-mRNA splicing factors [small nuclear ribonucleoproteins (snRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…It should be also noted that P. communis diplotene oocytes used in this study are transcriptionally inert [17] and, in contrast to the active cells, the IGC granules of P. communis oocytes could be the storage sites for the Pol II holoenzyme components disengaged from transcription. The same function of IGCs in inactive insect oocytes was discussed earlier [6,8]. Additionally, our data on tight association of transcriptional coactivators CBP/p300 with granules of IGCs in P. communis oocytes (Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It should be also noted that P. communis diplotene oocytes used in this study are transcriptionally inert [17] and, in contrast to the active cells, the IGC granules of P. communis oocytes could be the storage sites for the Pol II holoenzyme components disengaged from transcription. The same function of IGCs in inactive insect oocytes was discussed earlier [6,8]. Additionally, our data on tight association of transcriptional coactivators CBP/p300 with granules of IGCs in P. communis oocytes (Fig.…”
Section: Resultssupporting
confidence: 84%
“…The nature of some characteristic inclusions observed in oocytes of different insects as the CBs are established now [2][3][4][5] whereas until recently little is known about insect oocyte IGC structure and functions. Insect oocyte IGCs have been described only in a beetle [6,7], the house cricket [8], a fleshfly [9] and some bugs [10]. In our previous study, we showed some features of IGC structure and molecular composition in oocyte nuclei of the scorpionfly, Panorpa communis [11].…”
Section: Introductionmentioning
confidence: 93%
“…Le nom de « karyosphère » est préféré par Gruzova & Parfenov (1993). En réalité, cette structure est retrouvée dans tous les ovarioles méroïstiques étudiés (Bogolyubov et al 2000). Nous l'appelons ici : caryonucléole.…”
Section: Evolution Du Nucléole : Le Caryosome (Ou Caryonucléole)unclassified
“…Unfortunately, we still know very little about this subject. To date, IGC counterparts have been described only in some insects including the mealworm beetle, (37,38) the scorpionfly, (39) the house cricket, (40) some bugs, (41) and a fleshfly; (42) however, other ''granular'' NBs, resembling IGCs but of an unknown nature, have also been described in the oocytes of Drosophila, (43) the tse-tse fly, (44) and the dragonfly. (45) In many cases, insect oocyte IGCs possess peculiarities that make them somewhat different from the ''classic'' IGCs of mammalian somatic cells.…”
Section: The Interchromatin Granule Clustera Constantly Upgraded Orgamentioning
confidence: 99%
“…1). (37)(38)(39)(40)(41)(42) Fibrillar areas may occupy a significant portion of the IGCs in insect oocytes. It is unclear whether these fibrillar zones correspond to the socalled interchromatin granule associated zones (IGAZ) described in mammalian cells, (46) but some immunocytochemical data (39,41) suggest that these two zones constitute different IGC subdomains.…”
Section: The Interchromatin Granule Clustera Constantly Upgraded Orgamentioning
confidence: 99%